Fluvial processes in geomorphology - Leopold, Luna B. 1915-2006 (Dover Publications, 1995)
A pioneering study of landform development under processes associated with running water, this text encompasses both field and laboratory research. Topics include the landscapes of mountains, rivers, and seacoasts; studies of weathering, climate, and erosion; and coverage of geochronology, drainage patterns, channel changes, and the evolution of hill slopes. 1964 edition.
"An unabridged and unaltered republication of the work first published by W.H. Freeman and Company, San Francisco, in 1964"--T.p. verso.
Keywords: Physical geography.; Rivers.; elektronické knihy; electronic books